2003
DOI: 10.1016/s0896-6273(03)00751-7
|View full text |Cite
|
Sign up to set email alerts
|

Humor Modulates the Mesolimbic Reward Centers

Abstract: Humor plays an essential role in many facets of human life including psychological, social, and somatic functioning. Recently, neuroimaging has been applied to this critical human attribute, shedding light on the affective, cognitive, and motor networks involved in humor processing. To date, however, researchers have failed to demonstrate the subcortical correlates of the most fundamental feature of humor-reward. In an effort to elucidate the neurobiological substrate that subserves the reward components of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
292
5
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(337 citation statements)
references
References 54 publications
28
292
5
11
Order By: Relevance
“…This finding is in contrast to research on certain other personality traits, in particular to findings on "extraversion" and "neuroticism", which both showed robust correlations with BOLD response in limbic brain areas such as the amygdalae [5]. Activation in limbic brain areas was detected in most imagingstudies on humor appreciation as well [14,17,22,24,43].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This finding is in contrast to research on certain other personality traits, in particular to findings on "extraversion" and "neuroticism", which both showed robust correlations with BOLD response in limbic brain areas such as the amygdalae [5]. Activation in limbic brain areas was detected in most imagingstudies on humor appreciation as well [14,17,22,24,43].…”
Section: Discussioncontrasting
confidence: 96%
“…Notably, some of the regions found to be activated in these studies on personality traits were also found to be activated in brain imaging studies on humor appreciation. A number of studies have investigated the neural correlates of humor appreciation with functional magnetic resonance [3,13,14,22,24,25,35,39,43] and PET [17] (see [41] and [43] for an overview). The regions shown to be activated during humor appreciation in these studies included both cortical regions (such as the left inferior frontal gyrus [25,43], medial frontal [13], anterior [13,14,43] and posterior temporal [13,14,35] gyri) as well as subcortical nuclei (such as the caudate [14] and nucleus accumbens [17]) and limbic structures (such as the hippocampus [14] or amygdalae [24]).…”
Section: Introductionmentioning
confidence: 99%
“…Recent functional magnetic resonance imaging (fMRI) studies have sought to circumscribe areas that are involved in humor processing and its appreciation using jokes, cartoons or funny movies (e.g., Azim, Mobbs, Jo, Menon, & Reiss, 2005;Bartolo, Benuzzi, Nocetti, Baraldi, & Nichelli, 2006;Goel & Dolan, 2001;Mobbs, Greicius, Abdel-Azim, Menon, & Reiss, 2003;Mobbs, Hagan, Azim, Menon, & Reiss, 2005;Moran, Wig, Adams, Janata, & Kelley, 2004;Sieboerger, Ferstl, Volkmann, & von Cramon, 2004;Watson, Matthews, & Allman, 2006;Wild et al, 2006). A wide area around the temporo-parietal junction (temporo-occipital junction, posterior superior temporal sulcus, posterior middle temporal gyrus, in the following called TPJ), temporal pole and inferior frontal gyrus (IFG) is assumed to be involved in cognitive humor processing (e.g., Goel & Dolan, 2001;Mobbs et al, 2003;Moran et al, 2004;Wild et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A wide area around the temporo-parietal junction (temporo-occipital junction, posterior superior temporal sulcus, posterior middle temporal gyrus, in the following called TPJ), temporal pole and inferior frontal gyrus (IFG) is assumed to be involved in cognitive humor processing (e.g., Goel & Dolan, 2001;Mobbs et al, 2003;Moran et al, 2004;Wild et al, 2006). Most of the fMRI studies that have investigated neurologically healthy subjects found a more left-sided network.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging the neural substrates of humour Using fMRI, Allan Reiss and his colleagues at Stanford University measured the brain response in sixteen volunteers who were exposed to humorous cartoons in the scanner [2]. In an event-related design, the subjects categorized the cartoons as 'Funny' or 'Not Funny', and these categories were subsequently used with each subject to determine which brain regions were relatively activated by humour.…”
mentioning
confidence: 99%